2D Nanosheets of Mo2C/CoMoS4 as Active Electrocatalyst for Water Splitting. Issue 22 (13th October 2021) - Liu, Pan; Wang, Sumin; Quan, Yufei; Shen, Zhiruo; Wang, Qiguan
Abstract : 2D composited nanosheets of Mo2 C/CoMoS4 are synthesized by a hydrothermal approach to obtain a bifunctional water‐splitting electrocatalyst for hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) in aqueous alkaline solution. Due to the richened defects formed on the 2D catalyst, the as‐derived Mo2 C/CoMoS4 exhibits high activity. At 10 mA cm −2, the HER and OER overpotentials of the 2D Mo2 C/CoMoS4 nanosheets are just 117 and 250 mV, respectively, with the corresponding Tafel slope of 90 and 75 mV dec −1, near to the commercial Pt/C and IrO2 . X‐ray photoelectron spectroscopy proves the strong interactions between Mo2 C and CoMoS4 and the Raman analysis certifies the presence of richened defects in Mo2 C/CoMoS4 . Moreover, the Mo2 C/CoMoS4 possesses a long‐term catalytic stability, showing potential application in the water splitting. Abstract : 2D nanosheets of Mo2 C/CoMoS4 are synthesized by a hydrothermal method. Resulted from the surface‐engineering‐induced defects by combination of Mo2 C and CoMoS4, the 2D Mo2 C/CoMoS4 catalysts exhibit the excellent bifunctional activity, with low overpotentials of 250 mV for oxygen evolution reaction (OER) and 117 mV for hydrogen evolution reaction (HER) at 10 mA cm −2 . The 2D catalysts possess a long‐term stability, showing good application prospect.